Combined Laser-Doppler Flowmetry and Spectrophotometry: Feasibility Study of a Novel Device for Monitoring Local Cortical Microcirculation during Aneurysm Surgery - Sommer, Bjoern; Kreuzer, Maximilian; Bischoff, Barbara; Wolf, Dennis; Schmitt, Hubert; Eyüpoglu, Ilker Yasin; Roessler, Karl; Buchfelder, Michael; Ganslandt, Oliver Thomas; Wiendieck, Kurt (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2017)
Background Monitoring of cortical cerebral perfusion is essential, especially in neurovascular surgery. Study Aims To test a novel noninvasive laser-Doppler flowmetry and spectrophotometry device for feasibility during elective cerebral aneurysm surgery. Material and Methods In this prospective single-institution nonrandomized trial, we studied local cerebral microcirculation using the noninvasive laser-Doppler spectrophotometer "Oxygen-to-see" (O2C) in 20 consecutive patients (15 female, 5 male; median age: 60.5 ± 11.7 years) who were operated on for incidental cerebral aneurysms. Capillary-venous oxygenation (oxygen saturation ["SO2"]), postcapillary venous filling pressures (relative hemoglobin content ["rHb"]), blood cell velocity ("velo"), and blood flow ("flow") were measured in 7-mm tissue depth using a subdural fiberoptic probe. Results Representative recordings were acquired immediately after dural opening over a median time span of 88 ± 21.8 seconds (range: 60-128 seconds) before surgical manipulation. Baseline values (median ± 2 standard deviations) of brain perfusion as measured with the O2C device were SO2, 39 ± 16.6%; rHb, 53 ± 18.6 arbitrary units (AU); velo, 60 ± 20.4 AU; and flow, 311 ± 72.8 AU. Placement of the self-retaining retractor led to a decrease in SO2 of 17% ± 29% (p < .05) and flow of 10% ± 11% (p < .01); rHb increased by 18% ± 20% (p < .01), and velo remained unchanged. Retractor removal caused the opposite with an increased flow of 10% ± 7% (p < 0.001) and velo (3% ± 6%, p = 0.11), but a decrease in SO2 of 24% ± 33% (p = 0.09) and rHb of 12% ± 20% (p =0.18). No neurologic or surgical complications occurred. Conclusion Using this novel noninvasive system, we were able to measure local cerebral microcirculation during aneurysm surgery. Our data indicate that this device is able to detect changes during routine neurosurgical maneuvers. Thus it may be useful for early detection of cerebral microcirculatory disturbance
EVALuna2:16739

Erratum zu: Vena-subclavia-Katheter und Pneumothoraxrisiko: Maschinelle Beatmung erhöht das Pneumothoraxrisiko während infraklavikulärer landmarkengestützter V.‑subclavia-Punktion: eine prospektiv randomisierte Studie (Der Anaesthesist, (2019), 68, 5, (309-316), 10.1007/s00101-019-0579-x) - Palmaers, T.; Frank, P.; Eismann, H.; Sieg, L.; Leffler, A.; Schmitt, Hubert; Scholler, A. (Anaesthesist, 2019)
CRIS-Team Scopus Importer:2019-05-21

Improved Postoperative Facial Nerve and Hearing Function in Retrosigmoid Vestibular Schwannoma Surgery Significantly Associated with Semisitting Position - Roessler, Karl; Krawagna, Maximilian; Bischoff, Barbara; Rampp, Stefan; Ganslandt, Oliver Thomas; Iro, Heinrich; Schmitt, Hubert; Buchfelder, Michael (World Neurosurgery, 2016)
The pros and cons of semisitting positioning (SSP) versus lateral, horizontal positioning (LP) during retrosigmoid vestibular schwannoma (VS) surgery, especially concerning postoperative cranial nerve and brain stem preservation, are under continuous discussion.In a single-center retrospective cohort study, 30 VSs operated on in SSP compared with 30 operated on in LP with comparable demography were analyzed. During SSP surgery, transesophageal echocardiographic monitoring for venous air embolism was used continuously. Electrophysiologic cranial nerve monitoring was used in both groups.Length of surgery was significantly different between both groups: 183 minutes mean in SSP surgery versus 365 minutes mean in LP surgery (P = 0.0001). Postoperative rates of facial palsy and hearing loss were also significantly different. Six months postoperatively, 63% had normal facial nerve function after SSP surgery, whereas in LP surgery, 40% had no facial palsy (P = 0.02). Hearing preservation rate was also significantly different: 44% in SSP surgery compared with 14% in LP surgery who had preserved hearing (P = 0.006). Because of cerebrospinal fluid leaks, there were 3 operative revisions in the LP group (10%) and 1 (3.3%) in the SSP group. A clinically insignificant venous air embolism rate was found in 3.3% of patients (1/30) during SSP surgery. The neurologic outcome after 6 months was 1.2 on the Rankin Scale in the LP group and 1.0 in the SSP group, with zero mortality.SSP compared with LP surgery was associated with significantly shorter operation time and better facial and cochlear nerve function in VS surgery postoperatively, without differences in complication rate
EVALuna2:16715

Intraoperative continuous cerebral microcirculation measurement in patients with aneurysmal subarachnoid hemorrhage: preliminary data on the early administration of magnesium sulfate - Sommer, Bjoern; Weidinger, Cornelia; Wolf, Dennis; Buchfelder, Michael; Schmitt, Hubert (BMC Anesthesiology, 2017)
BACKGROUND: In patients with subarachnoid hemorrhage (SAH), vasospasm remains one of the major complications. The application of intravenous magnesium sulfate (MgSO4) has been under discussion to prevent cerebral ischemia. Our aim was to examine the impact of early MgSO4 administration on local cerebral microcirculation during microsurgical clipping of SAH-related aneurysms. METHODS: The non-invasive laser-Doppler spectrophotometry system "Oxygen-to-See (O2C)" was used in 14 consecutive patients (11 female, 3 male, median age 56.5±9.7 yrs) with aneurysmatic SAH. A subdural probe measured capillary venous oxygenation (SO2), relative hemoglobin content (rHb), blood cell velocity (velo) and blood flow (flow) in 7 mm tissue depth. Data samples were recorded as baseline immediately before intraoperative application of MgSO4 10% 50 mg/kg body weight and 10 min thereafter. The continuous MgSO4 infusion rate depended on blood pressure (mean arterial pressure > 60-65 mmHg) and lasted a maximum of 60 min. RESULTS: MgSO4 was administered 2.8 (min. 1.6, max. 15.5) hours after onset of symptoms. Median flow increased significantly by 20.8% (5-68%, p = 0.001). Velo increased 4.9% (1-17%), rHb decreased 1.5% (3-34%) and SO2 decreased 9.4% (8-38%) by trend compared to the baseline values. FiO2 correlated positively with velo (rs = 0.712, p = 0.004), whereas arterial HCO3 correlated negatively with SO2 (rs = -0.599, p = 0.024). Of 14 patients, 2 had symptomatic vasospasm. CONCLUSIONS: Our data suggest an increased cerebral blood flow after early intraoperative administration of MgSO4 in patients with SAH. Using a non-invasive laser-Doppler spectrophotometry system, this technique is feasible for continuous real-time monitoring of cerebral microcirculation. TRIAL REGISTRATION: DRKS (German Clinical Trial Registry), DRKS00013047 , retrospectively registered on September 21st, 2017.
EVALuna2:35115

Intraoperative Vascular Neuromonitoring in Patients with Subarachnoid Hemorrhage: A Pilot Study Using Combined Laser-Doppler Spectrophotometry - Schmitz, Emilija; Bischoff, Barbara; Wolf, Dennis; Schmitt, Hubert; Eyupoglu, Ilker Y.; Roessler, Karl; Buchfelder, Michael; Sommer, Bjoern (World Neurosurgery, 2017)
BACKGROUND: Intraoperative monitoring of cerebral microcirculation in patients with subarachnoid hemorrhage (SAH) may predict the postoperative neurologic outcome. In this pilot study, we examined the value of a novel noninvasive real-time measurement technique for detecting changes in local microcirculation. METHODS: We used the O2C (Oxygen to see) laser-Doppler spectrophotometry system in 14 patients with Hunt & Hess grade 2-5 SAH who underwent microsurgical cerebral aneurysm clipping. A subdural probe recorded capillary venous oxygenation (SO2), relative hemoglobin concentration, blood cell velocity, and blood flow at a tissue depth of 7 mm. Data were recorded immediately before dural closure. We also recorded somatosensory evoked potentials (SEPs) with median and tibial nerve stimulation. Results were compared with neurologic performance, as measured on the modified Rankin Scale, at the day of discharge from the hospital and 12 months thereafter. RESULTS: Patient functional outcomes after discharge and 12 months were correlated with pathological decreased flow and increased SO2 values. In 6 of 8 patients, microcirculatory monitoring parameters indicated ischemia during surgery, as shown by electrophysiological SEP changes and infarction detected on the postoperative computed tomography (CT) scan. Pathological SEP results correlated closely with infarct demarcation as seen on CT. CONCLUSIONS: Our results indicate the potential benefit of intraoperative combined laser-Doppler flowmetry and spectrophotometry for predicting postoperative clinical outcomes in this small patient sample. Larger-cohort testing is needed to verify our findings and show the possible merits of this novel method.
EVALuna2:35113

Pedicle screw instrumentation of the cervicothoracic junction in the sitting position using ct-guided navigation: Application and technical aspects - Hore, Nirjhar; Lücking, Hannes; Schmitt, Hubert; Buchfelder, Michael; Brandner, Sebastian (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2021)
Background We evaluate the feasibility and potential advantages of spinal CT navigation in the placement of pedicle screws at the cervicothoracic junction in the sitting position to counteract the anatomy-related limitations of 2D fluoroscopy. Methods We retrospectively analyze the data from 15 patients who underwent CT-based navigation-guided placement of a total of 36 pedicle screws at the cervicothoracic junction in the sitting position. Results CT-based spinal navigation is a useful method in increasing accuracy of pedicle screw instrumentation in the sitting position, successfully counteracting the anatomy-related limitations of 2D fluoroscopy at the cervicothoracic junction. Conclusion CT-based navigation-guided placement of pedicle screws at the cervicothoracic junction in the sitting position proved to be an accurate, safe, and user-friendly method.
CRIS-Team Scopus Importer:2021-02-26
Keywords: Cervical spine; Sitting position; Spinal navigation

Small doses of epinephrine prolong the recovery from a rocuronium-induced neuromuscular block: a case report - Schmitt, Hubert (BMC Anesthesiology, 2018)
BACKGROUND: During anaesthesia it is not uncommon to administer epinephrine in patients blocked by non-depolarizing muscle relaxants. However, there are few reports on possible interaction of epinephrine with neuromuscular transmission in humans. CASE PRESENTATION: An otherwise healthy 74-yr-old man underwent transurethral resection of a benign prostatic hyperplasia under total intravenous anaesthesia. Because of repeated drop in heart rate and blood pressure the patient received in total three bolus of epinephrine 5 μg, respectively. Each time this small dose of epinephrine intensified a rocuronium-induced neuromuscular block verified by acceleromygraphy. Further anaesthetic course was uneventful. CONCLUSIONS: In this case reported here small doses of intravenously administered epinephrine markedly prolonged a rocuronium-induced neuromuscular block. Given the widely used co-administration of epinephrine and muscle relaxants possible adrenergic interference with neuromuscular transmission would have implications for daily anaesthetic practice.
EVALuna2:212909

Vena-subclavia-Katheter und Pneumothoraxrisiko: Maschinelle Beatmung erhöht das Pneumothoraxrisiko während infraklavikulärer landmarkengestützter V.‑subclavia-Punktion: eine prospektive randomisierte Studie - Palmaers, T.; Frank, P.; Eismann, H.; Sieg, L.; Leffler, A.; Schmitt, Hubert; Scholler, A. (Anaesthesist, 2019)
Background: Infraclavicular subclavian vein (SCV) catheterization is a standard procedure in anesthesia and intensive care. There is a lack of evidence on how mechanical ventilation during venipuncture of the SCV influences pneumothorax rates. Objective: Primary hypothesis: non-inferiority of continuing vs. discontinuing mechanical ventilation during infraclavicular puncture of the SCV with respect to the pneumothorax rate. Material and methods: This prospective, randomized and single-blinded study was approved by the local ethics committee. A total of 1021 eligible patients who underwent cranial neurosurgery in 2 different university hospitals were assessed between August 2014 and October 2017. Patients were randomly assigned to two groups directly before induction of anesthesia. Intervention groups for venipuncture of the SCV were mechanical ventilation: tidal volume 7 ml/kg ideal body weight, positive end expiratory pressure (PEEP) ideal body weight/10, n = 535, or apnea: manual/spontaneous, APL valve 0 mbar, n = 486. Patients and the physicians who assessed pneumothorax rates were blinded to the intervention group. Venipuncture was carried out by both inexperienced and experienced physicians. Results: The pneumothorax rate was significantly higher in the mechanical ventilation group (2.2% vs. 0.4%; p = 0.012) with an odds ratio (OR) of 5.63 (95% confidence interval, CI: 1.17–27.2; p = 0.031). A lower body mass index (BMI) was associated with a higher pneumothorax rate, OR 0.89 (95% CI: 0.70–0.96; p = 0.013). Conclusion: In this study landmark-guided infraclavicular SCV catheterization was associated with a significantly higher rate of pneumothorax when venipuncture was performed during mechanical ventilation and not in apnea. If a short phase of apnea is justifiable in the patient, mechanical ventilation should be discontinued during the venipuncture procedure.
CRIS-Team Scopus Importer:2019-05-24
Keywords: Central venous catheter; Complication; Pneumothorax; Subclavian vein